Smakelijk eten, allemaal - Lambrechts, An; Vannoppen, Jan; Boutsen, Saartje; Dessers, David (Gent: Oxfam-Wereldwinkels, 2006)
"redactie: An Lambrechts, Jan Vannoppen, Saartje Boutsen ; eindredactie: David Dessers"